The Iowa state constitution - Stark, Jack, 1939- (Oxford commentaries on the state constitutions of the United States., 2011)
"The Iowa State Constitution is the first comprehensive analysis of the Iowa Constitution and its individual provisions. In it, Jack Stark presents a comprehensive overview of Iowa's constitutional historical development and discusses cases of particular importance. Also included are a bibliographic essay, table of cases, tables relating to constitutional conventions and amendments, and a general index, offering significant sources for further study. The Oxford Commentaries on the State Constitutions of the United States is an important new series that reflects a renewed international interest in constitutional history and provides expert insight into each of the 50 state constitutions. Each volume in this innovative series contains a historical overview of the state's constitutional development, a section-by-section analysis of its current constitution, and a comprehensive guide to further research. Under the expert editorship of Professor G. Alan Tarr, Director of the Center on State Constitutional Studies at Rutgers University, this series provides essential reference tools for understanding state constitutional law. Books in the series can be purchased individually or as part of a complete set, giving readers unmatched access to these important political documents"--